Juridical Analysis Of Human Rights Protection For Indonesian Migrant Workers Shipped Illegally : Research Study At The Riau Islands Police Directorate - Salamun Salamun; Bachtiar Simatupang; Ramlan Ramlan; Soerya Respationo; Erniyanti Erniyanti (LITERACY : International Scientific Journals of Social, Education, Humanities, 2024)
This research focuses on "Juridical Analysis of Human Rights Protection of Indonesian Migrant Workers Sent Illegally (Research Study at the Directorate of Criminal Investigation of the Riau Islands Police)". The background of this study is based on the increasing number of cases of Indonesian migrant workers being sent illegally in the Riau Islands, a region that has an important role as an exit point for many migrant workers abroad. This reflects the urgent need to examine the extent of the effectiveness of the law and human rights protections provided to migrant workers. The purpose of this study is to analyze and evaluate the effectiveness of the implementation of human rights protection for illegally sent migrant workers, as well as to identify obstacles and solutions in the implementation of such protection by the Riau Islands Police Directorate of Criminal Investigation. This study uses normative and empirical juridical research methods, combining analysis of legal documents and in-depth interviews with stakeholders involved, including law enforcement officials, victims, and NGOs involved in migration issues. The results show that although there is a legal framework that includes the Migrant Worker Protection Law and the Human Rights Law, there are still weaknesses in its implementation. The main obstacles identified include limited resources, ineffective interagency coordination, and low legal awareness among migrant workers. Based on these results, the suggestions submitted include increasing the allocation of resources for the Directorate of Criminal Investigation to strengthen investigations and enforcement, improve the inter-agency coordination system, and increase education programs for the public about their rights as migrant workers. This advice is expected to help strengthen human rights protections for Indonesian migrant workers who are sent illegally.